2011
DOI: 10.1111/j.1540-8167.2011.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

The Electroanatomic Mechanisms of Atrial Tachycardia in Patients with Tetralogy of Fallot and Double Outlet Right Ventricle

Abstract: The CTI and lateral RA wall are critical corridors of conduction in 85% of IART circuits in TOF and DORV patients. The acute success rate for AT ablations is high, but a substantial number of patients have required additional ablation procedures. Recurrences may be reduced if both the CTI and lateral RA wall are targeted and blocked, even if the mapped circuit points only to 1 region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Though initial success rate for AT ablations was high, 19% of the patients experienced recurrent sustained AT within 6.5 months of follow-up [78]. Recurrence rate may decrease if both the CTI and lateral RA wall are ablated, even if single substrate region is detected by mapping [77].…”
Section: Catheter-based Ablation Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Though initial success rate for AT ablations was high, 19% of the patients experienced recurrent sustained AT within 6.5 months of follow-up [78]. Recurrence rate may decrease if both the CTI and lateral RA wall are ablated, even if single substrate region is detected by mapping [77].…”
Section: Catheter-based Ablation Therapymentioning
confidence: 99%
“…The success rate for treating VTs in rTOF patients by ablation varies from 50% to 91% according to the studies using electroanatomic substrate-based mapping approach [74,75]. Described VT recurrence rates remain high (up to 20%) in turn hindering wider use of this treatment strategy in patients with rTOF [76,77]. Effective ablation is even more complicated to achieve in patients who are haemodynamically unstable during VT.…”
Section: Catheter-based Ablation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Distinctive patterns for IART circuit location have been uncovered that vary according to underlying CHD lesion and method of repair, allowing one to predict with reasonable certainty the location of usual suspect sites for productive ablation. 8,9,[21][22][23] To take advantage of these patterns, intracardiac and venous anatomy must be well understood. Operative notes are mandatory reading because surgical techniques vary significantly among patients, surgeons, and eras.…”
Section: Ablation For Iart In Chdmentioning
confidence: 99%
“…These can include classic atrial flutter through the cavotricuspid isthmus, as well as atypical circuits related to atriotomy incisions and other scars. 8,9 The general term intra-atrial reentrant tachycardia (IART) has been used to describe all these circuits in CHD. Focal atrial tachycardia can also be observed in a small number of patients, usually arising from locations mapped in close proximity to a scar zone.…”
Section: Atrial Tachycardiasmentioning
confidence: 99%